Functional richness shows spatial scale dependency in Pheidole ant assemblages from Neotropical savannas. Issue 20 (27th September 2019) - Neves, Karen; Moura, Mario R.; Maravalhas, Jonas; Pacheco, Renata; Pie, Marcio R.; Schultz, Ted R.; Vasconcelos, Heraldo L.
Abstract: There is a growing recognition that spatial scale is important for understanding ecological processes shaping community membership, but empirical evidence on this topic is still scarce. Ecological processes such as environmental filtering can decrease functional differences among species and promote functional clustering of species assemblages, whereas interspecific competition can do the opposite. These different ecological processes are expected to take place at different spatial scales, with competition being more likely at finer scales and environmental filtering most likely at coarser scales. We used a comprehensive dataset on species assemblages of a dominant ant genus, Pheidole, in the Cerrado (savanna) biodiversity hotspot to ask how functional richness relates to species richness gradients and whether such relationships vary across spatial scales. Functional richness of Pheidole assemblages decreased with increasing species richness, but such relationship did not vary across different spatial scales. Species were more functionally dissimilar at finer spatial scales, and functional richness increased less than expected with increasing species richness. Our results indicate a tighter packing of the functional volume as richness increases and point out to a primary role for environmental filtering in shaping membership of Pheidole assemblages in Neotropical savannas. OPEN RESEARCH BADGES: This article has been awarded Open Materials, Open Data, Preregistered Research Designs Badges. All materials and data are publicly accessible via the Open Science Framework at https://doi.org/10.5061/dryad.31201jg Abstract : Pheidole ant assemblages from Neotropical savannas are more functionally similar at coarser than finer spatial scales. Our findings point out to a tighter packing of the functional volume of ant assemblages as richness increases, suggesting the primary role of environmental filtering in shaping membership of Pheidole assemblages in Neotropical savannas.